2000
DOI: 10.1034/j.1600-0404.2000.102006350.x
|View full text |Cite
|
Sign up to set email alerts
|

The butyrylcholinesterase K variant is a protective factor for sporadic Alzheimer's disease in women

Abstract: Our study is the first to demonstrate that lower susceptibility to AD determined by the K variant of BCHE is dependent on gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 7 publications
3
19
0
3
Order By: Relevance
“…However, this relationship has been disputed by other authors [41]. More recently, analysis of K variant and ApoE4 allelic frequencies for a population in Spain revealed that the K-variant form of BuChE may provide a protective effect for sporadic AD, although this effect was only seen for women [42]. The observation that BuChE mutations affect disease susceptibility adds further support to the idea that BuChE plays an important role in AD.…”
Section: Buche Polymorphisms As a Risk Factor For Admentioning
confidence: 57%
“…However, this relationship has been disputed by other authors [41]. More recently, analysis of K variant and ApoE4 allelic frequencies for a population in Spain revealed that the K-variant form of BuChE may provide a protective effect for sporadic AD, although this effect was only seen for women [42]. The observation that BuChE mutations affect disease susceptibility adds further support to the idea that BuChE plays an important role in AD.…”
Section: Buche Polymorphisms As a Risk Factor For Admentioning
confidence: 57%
“…Numerous studies have examined whether BuChE variants (usually the "atypical" and/or K variants) are associated with Alzheimer's disease. The results have not been consistent (Lehmann et al, 2001), although several have found that the low activity alleles seem to be associated with lower susceptibility to AD and/or later age of onset (Alvarez-Arcaya et al, 2000;Lane et al, 2006Lane et al, , 2008Mateo et al, 2008), or a significantly reduced rate of progression of cognitive decline in individuals with severe AD (Holmes et al, 2005). The presence of the K variant has also been associated with lower benefits from rivastigmine treatment (Bullock et al, 2005).…”
Section: Vic Is Inhibition Of Buche Appropriately Consideredmentioning
confidence: 61%
“…[39][40][41] Some groups have reported a protective effect of BCHE-K genotype on the risk of AD. [42][43][44] A meta-analysis of all published association studies indicates that BCHE-K does not influence the risk of AD (odds ratio (OR) 1.08, 95% confidence interval (CI) 0.96-1.22) (http://www.alzgene. org).…”
Section: Introductionmentioning
confidence: 99%